Pengaruh Cara Pengolahan terhadap Karakteristik Fisiokimia Tapioka - Rejeki, Sri (Jurnal Gizi Ilmiah, 2014)
Some of the tapioca processing industries have been classified as advanced industries and some are still traditional. Traditional food industries are generally small scale. These various characteristics of the industry are caused by relatively small capital, relatively high maintenance costs, generally simple technology, generally low product quality, and limited access to markets. The processing technology used can be grouped into three, namely: first; the traditional tapioca processing industry which still relies on sunlight and its production is highly dependent on the seasons, second; semi-modern namely tapioca processing industry that uses a drying machine (oven) in the drying process and the third; Modern technology is the tapioca processing industry that uses machines from the initial process to the finished product. The modern tapioca industry uses fully automated equipment that has high efficiency, because the production process requires less labor, shorter time and produces quality tapioca. One of the advantages of traditional tapioca is that it expands well during oven development (Camargo et al., 1988) and frying. This type of starch is very much needed by the food industry, such as the atomic bean or cracker industry which can provide great benefits because with a small amount of starch it can produce large volumes of food products. In this study, 15 samples of starch were used consisting of 5 types of samples from modern industry, 5 types of samples from semi-modern industries and 5 types of samples from traditional industries. The analysis carried out included analysis of water content, ash content, protein content, starch content, amylose content, swelling power and solubility, specific volume of starch development (baking expansion and frying expansion), starch microscopy, amylographic properties, clarity of starch gel, acidity and white degree. The physicochemical characteristics of cassava starch vary between modern, semi-modern and traditional industries, which are influenced by the processing process. The results showed that traditional processing showed the best results with the development value of the baking expansion process of 9.25-11.97 ml/g, frying expansion of 8.38-11.09 ml/g, amylose of 21.49 -30.89%, swelling power of 10.07-15.79 g/g, solubility of 23.65-34.63% and viscosity of paste 1139.2-2782.4Cp.